Urinary 5-hydroxyindoleacetic acid in 8-hour collections as an aid in diagnosis of coeliac disease. Issue 10 (October 1975) - Challacombe, D N; Goodall, M; Gaze, H; Brown, G A
Abstract : 8-hour urine excretions of 5-hydroxyindoleacetic acid (5-HIAA) were measured in 18 children with coeliac disease before treatment and the results expressed as microgram 5-HIAA/mg creatinine. Similar measurements were made on urine collections from an age-matched control group of 24 children. Significantly higher values of 5-HIAA excretion were found in children with untreated coeliac disease. Measurement of the 5-HIAA: creatinine ratio in 8-hour urine collections is therefore proposed as an aid in the diagnosis of coeliac disease.